IMPLEMENTASI NILAI-NILAI KEBUDAYAAN DALAM PRAKTIK BIMBINGAN DAN KONSELING DI INDONESIA [IMPLEMENTATION OF CULTURAL VALUES IN GUIDANCE AND COUNSELING PRACTICES IN INDONESIA] - Rara Eka Yurika; Adhitya Ridwan Budhi Prasetyo Nugroho (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2022)
Indonesia was a country that has a variety of cultures. The implementation of cultural values in the practice of guidance and counseling in Indonesia was important because humans and culture were a unified whole. The purpose of this study was to identify and describe the implementation of cultural values in the practice of guidance and counseling in Indonesia. The method used in this research was a literature review. The results of this study indicated that there were Indonesian cultural values that can be implemented into the practice of guidance and counseling. These cultural values were interpreted and analyzed so that they can be implemented in guidance and counseling services. There were several community groups whose cultural values have been implemented, such as the cultural values of the Bangka Malay people, the cultural values of the Javanese people, the cultural values of the Sasak people, the cultural values of the people of South Kalimantan, and the cultural values of the people of West Kalimantan.